Mupperuṅ kāviyaṅkaḷil oṉṟāṉa Maṇimēkalai ārāycci - Turaicāmip Piḷḷai, Auvai Cu., 1903- (SAMP early 20th-century Indian books project ;, 1942)
Study of Maṇimēkalai, a classical Sangam epic, by Cāttaṉar.